Tinjauan holistik terhadap pendekatan pembelajaran matematika: Meningkatkan pemahaman dan minat siswa - Mukhlisoh, Yeni (Maliki Interdisciplinary Journal, 2024)
This article discusses a holistic review of mathematics learning approaches aimed at enhancing students' understanding and interest in the subject. In today's educational environment, a comprehensive and diverse approach is needed to address challenges in mathematics learning. Through a holistic review, this article analyzes various teaching methods, instructional strategies, and psychosocial factors that influence students' mathematics learning outcomes. Approaches emphasizing the connection between mathematical concepts and the real world, technology integration, and student engagement in the learning process can enhance their understanding and interest. The article also emphasizes the importance of support from the school environment, family, and adaptive curriculum in creating a learning environment that facilitates holistic student development. The results of this review indicate that a holistic mathematics learning approach can create more engaging, meaningful, and effective learning experiences for students.